Packet data communications over coded CDMA - Part II Throughput bound of CDMA unslotted ALOHA with hybrid type II ARQ using rate compatible punctured turbo codes. - Seokhyun Yoon (IEEE Transactions on wireless communications)
In this part of the paper, we investigate the throughput bound of CDMA unslotted ALOHA system with a hybrid type II automatic-repeat-request (ARQ) implemented using rate compatible punctured turbo codes. The system under consideration can be regarded as an enhanced version of the classical CDMA packet radio network. When applying a hybrid type-II ARQ, the probability of packet success and packet length is generally different from attempt to attempt. Since the conventional analytical model, customarily employed for the ALOHA system with pure or hybrid type-I ARQ, cannot be applied for this case, we introduce an expanded analytical model, which can be regarded as a network of queues, and apply Jackson and Burke's theorems to simplify the analysis. When using code combining, soft-decision decoding is usually considered, in which case, it is very difficult to find the actual probability of packet success, especially when the number of terminals changes during a packet time duration. Hence, instead of finding the actual probability of packet success, we evaluate a lower and an upper bound. Together with the expanded model and the packet success probability bound, we obtain the corresponding throughput bounds by iteratively searching the steady-state arrival rate, λ, and the average departure rate, μ, for given composite offered traffic, G=λ/μ. The results show that significant improvement in throughput can be achieved by exploiting high coding gain of turbo codes and channel utilization efficiency of incremental redundancy retransmission protocol.